(untitled) (Revista de História da UEG (REVHIST), 2025)
In this article I carry out an analysis derived from my doctoral thesis in Sociology on the relationships between collective memory, territoriality and identity in the city. Through sociological ethnography combined with documentary analysis, I followed events and rituals commemorating the anniversaries of Poço da Draga, one of the oldest occupations in Fortaleza. In the thesis, I analyzed community anniversaries, guided tours and Guardians of Memory circles (emic term), between 2014 and 2018, and how much these events allow us to understand the construction and legitimization of collective memory, activated in defense of that territory. In the article, I discuss specifically the material and symbolic connections of residents in relation to the Metallic Bridge, and what this represents about the construction of the memory of Fortaleza, a city that has no heritage tradition, but overflows with memory and invisible experiences. I understand the case of Poço da Draga as emblematic to reflect on the resistance and (r)existences in the city, in the sense of individual and collective memories and also of collective heritage that are not made visible by the Public Power, but that pulse and remain alive for others shared paths and struggles. Keywords: Memory. Heritage. City. Poço da Draga.